Spinal osteomyelitis due to Mycobacterium fortuitum in a former intravenous drug user. (10th July 2013) - Longardner, Katie; Allen, Ahkeel; Ramgopal, Moti
Abstract : A 47-year-old woman with a history of intravenous drug use presented to the emergency department with a 6-month history of pain in her lumbar back and right buttock. She had stopped injecting drugs 1 year ago. Physical examination was unremarkable except for paraspinal and right sacroiliac joint tenderness. MRI confirmed discitis, osteomyelitis and abscess formation in the L5–S1 disc space. She underwent extensive vertebral surgery and debridement of the spinal abscess. Her surgical cultures grew Mycobacterium fortuitum, and she was treated with an appropriate combination of intravenous antimicrobial therapy.